If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x*.6667=420.49
We simplify the equation to the form, which is simple to understand
x*.6667=420.49
Simplifying:
+ 0.6667x=420.49
We move all terms containing x to the left and all other terms to the right.
+ 0.6667x=+420.49
We simplify left and right side of the equation.
+ 0.6667x=+420.49
We divide both sides of the equation by 0.6667 to get x.
x=630.703464827
| 3[2(-y^2+y)-3]-3(2x+y)= | | 9x+5=9(x+6) | | 8x+2+2x=0 | | c-3=105 | | x+35=100 | | (15b-9)-7(2b+3)=-5 | | 2(x+y)+3x+2y= | | 9x+4x+4+9=5x+3+7x | | 6p+9=18+5p | | -2=-4x^2+12x+14 | | 7x=6x+2 | | 14=-4x^2+12x+14 | | 0.20(18)+0.05x=0.10(6+x) | | 28=x^2+9x+18 | | 4=x^2+9x+18 | | 3x+(-3y)-(4x)+y= | | 172-4x=23x+16 | | 2x^6w^4*2w^3*4x= | | 6=x^2-7x+12 | | 2=x^2-7x+12 | | 2x^2-x=120 | | 1.25x+0.125x=0.875+x | | 3x^2+9x=54 | | -16x^2+220x=0 | | 7+2x*5=x*6+11 | | -8x^3-20x^2=8x | | (5x+4)(3x-3)=0 | | x-8=4x | | 9x^2=51x-60 | | 6(t-5)+8t=7(2t+4)-11 | | 5t+2+4t-8t=5+5 | | 4(x-3)=-(x+7) |